Strategi Pengembangan Rantai Pasok Kentang Berkelanjutan di Kabupaten Magetan - Arum Hidayati; Heru Irianto; nFN Kusnandar (Jurnal Agro Ekonomi, 2018)
EnglishThe accelerating demand growth as reflected by significant increase of potato consumption per capita indicates high potential of potato development in Indonesia. Potato production in Magetan Regency in recent years, however, has been fluctuating, perhaps due to some weaknesses in its supply chains. The objective of this study, therefore, is to formulate a sustainable supply chain development strategy for potato in Magetan Regency. The study was conducted using the Sustainable Supply Chain Management perspective and the Analytical Network Process. The study was conducted in 2016. The results show that development of sustainable supply chain is the key for accelerating and stabilization of potato production growth. Although the economic dimension is the highest priority, the social and environmental dimensions are almost equally important as well. While varietal and technological choice should be based on the highest profit, it nevertheless should also be socially acceptable and environmentally friendly, such as the Granola variety in Magetan Regency. The priority actors are farmers, government, and traders (collectors and wholesalers). The priority strategic action programs are increasing potato farming product quality and productivity, increasing potato value added, and empowering of farmers and farmers’ groups.Keywords:  IndonesianAkselerasi pertumbuhan permintaan yang dicerminkan oleh peningkatan nyata konsumsi per kapita mengindikasikan bahwa kentang berpotensi besar untuk dikembangkan di Indonesia. Namun demikian, produksi kentang di Kabupaten Magetan dalam beberapa tahun terakhir ternyata berfluktuasi yang ditengarai akibat dari beberapa kelamahan pada rantai pasok. Sejalan dengan itu, penelitian ini bertujuan untuk merumuskan strategi pengembangan kinerja rantai pasok berkelanjutan untuk kentang di Kabupaten Magetan. Penelitian dilakukan dengan perspektif Sustainable Supply Chain Management dan metode analisis the Analytical Network Process. Penelitian dilakukan pada 2016. Penelitian menunjukkan bahwa pengembangan rantai pasok berkelanjutan adalah kunci untuk akselerasi dan stabilisasi produksi. Dimensi ekonomi merupakan prioritas utama, namun dimensi sosial dan lingkungan hampir sama pentingnya. Pemilihan varietas atau teknologi didasarkan pada keuntungan terbesar, namun juga diterima secara sosial dan ramah lingkungan, seperti varietas Granola di Kabupaten Magetan. Aktor terpenting ialah petani, pemerintah, dan pedagang (pengumpul dan pedagang besar). Program aksi strategis diprioritaskan pada peningkatan kualitas dan produktivitas usaha tani, peningkatan nilai tambah kentang, serta pemberdayaan petani dan kelompok tani.